Lower ungulate population density in rainforests under anthropogenic influences - Leite de Oliveira, Márcio; Grotta-Neto, Francisco [UNESP]; Rosa da Silva, Amanda [UNESP]; Pinho, Manoela Ebner; Ribeiro, Rullian César [UNESP]; de Almeida Correia Junior, Antônio; Jerozolimski, Ricardo; de Faria Peres, Pedro Henrique [UNESP]; Vogliotti, Alexandre; Duarte, José Maurício Barbanti [UNESP]; de Camargo Passos, Fernando (Wiley, 2025)
The main threats to forest ungulates are land cover change, poaching, invasive species and other anthropogenic factors. Tropical rainforest deer, especially those in the South American Atlantic Forest, are extremely elusive, resulting in limited data on their density and the factors influencing it. In this study, our objective was to estimate the density of Atlantic Forest deer and to identify its most significant drivers. We conducted density estimates using faecal standing crop methods with scat detection dogs across the whole Atlantic Forest. In addition, we investigated the influences on density of a locally collected environmental index (AII) incorporating anthropogenic impact variables, landscape metrics (habitat cover, matrix heterogeneity and number of habitat patches), altitude, slope, canopy height and socioeconomic indexes (human development index, purchasing power parity, income inequality and gender development index) as well as protected area ranger density. After a variable selection process to avoid autocorrelation, we tested the relationship between the selected variables and forest deer population density using multiple linear regression models. Density varied from 0.14 to 18.17 individuals/km2, with P. nemorivagus showing the highest values. The average and median values were 3.42 and 1.47 individuals/km2, respectively. Only the model where density was a function of AII was significant, with satisfactory residuals and the lowest AIC value. Synthesis and applications. Our results highlight how threats such as poaching, predation by domestic dogs, disease transmission from domestic ungulates and competition, predation or disturbance by wild boar may affect forest deer density and potentially lead to species extinction.
Keywords: abundance; Atlantic Forest; detection dogs; human impact; mammals